2020
DOI: 10.1093/icesjms/fsaa225
|View full text |Cite
|
Sign up to set email alerts
|

Trawl and eDNA assessment of marine fish diversity, seasonality, and relative abundance in coastal New Jersey, USA 

Abstract: Environmental DNA (eDNA) technology potentially improves the monitoring of marine fish populations. Realizing this promise awaits better understanding of how eDNA relates to fish presence and abundance. Here, we evaluate performance by comparing bottom trawl catches to eDNA from concurrent water samples. In conjunction with New Jersey Ocean Trawl Survey, 1-l water samples were collected at surface and depth prior to tows at about one-fourth of Survey sites in January, June, August, and November 2019. eDNA fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
188
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(198 citation statements)
references
References 50 publications
8
188
2
Order By: Relevance
“…Accordingly, eDNA-based investigations have proven to be as valuable as traditional survey methods that require capture and subsampling of target organisms. Importantly, eDNA methods are a less-intrusive approach to studying invasive or declining species (Zhou et al, 2013;Bucklin et al, 2016;Holman et al, 2019;Nelson-Chorney et al, 2019), documenting the distribution of difficult to sample taxa (Parsons et al, 2018), and estimating relative seasonal biomass of target species (Takasu et al, 2019;Stoeckle et al, 2020). Marine-derived eDNA has also been likened to a "barometer of disturbance" with respect to its potential to assess anthropogenic effects on ecosystems (Dibattista et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, eDNA-based investigations have proven to be as valuable as traditional survey methods that require capture and subsampling of target organisms. Importantly, eDNA methods are a less-intrusive approach to studying invasive or declining species (Zhou et al, 2013;Bucklin et al, 2016;Holman et al, 2019;Nelson-Chorney et al, 2019), documenting the distribution of difficult to sample taxa (Parsons et al, 2018), and estimating relative seasonal biomass of target species (Takasu et al, 2019;Stoeckle et al, 2020). Marine-derived eDNA has also been likened to a "barometer of disturbance" with respect to its potential to assess anthropogenic effects on ecosystems (Dibattista et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have demonstrated that eDNA barcoding can be employed to characterize the species composition of captured fish from the meltwater leftover in industrial and artisanal fishing operations. eDNA is gaining popularity and utility in fisheries and seafood research and has the potential to be a potent and complementary tool to the growing number of approaches to improving traceability throughout the seafood supply chain [ 38 , 40 , 54 , 55 ]. Built upon nearly two decades of studies applying the well-vetted concept of DNA barcoding to identify fish to species level [ 16 , 56 ], the eDNA approach is positioned to be both a familiar and a transformative tool in improving seafood monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we were unable to identify species relative abundance or biomass from a catch. The ability to use eDNA metabarcoding for abundance or biomass estimation remains equivocal [ 65 ], although recent applications appear promising [ 40 , 66 ]. Importantly, theoretical advancement in our understanding of PCR bias suggests that the application of mock communities can be strategically used to allow for the correction and estimation of abundance [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations